NOTE: This transcription was contributed by Martin P.M. van der Burgt, who has devised a process for producing transcripts automatically. Although its markup is incomplete, we believe it serves a useful purpose by virtue of its searchability and its accessibility to text-reading software. It will be replaced by a fully marked-up version when time permits. —HR

 Copyright Notice The following manuscript EWD 582 A proof of a theorem communicated to us by S.Ghosh (with C.S.Scholten) : is held in copyright by Springer-Verlag New York. The manuscript was published as pages 233–234 of Edsger W. Dijkstra, Selected Writings on Computing: A Personal Perspective, Springer-Verlag, 1982. ISBN 0–387–90652–5. Reproduced with permission from Springer-Verlag New York. Any further reproduction is strictly prohibited.

A proof of a theorem communicated to us by S.Ghosh.

by Edsger W.Dijkstra and C.S.Scholten

In a letter of 19 August 1976, S.Ghosh (currently c/o Lehrstuhl Informatik I, Universitat Dortmund, Western Germany) communicated without proof the following theorem in natural numbers —here chosen to mean “nonnegative integers”— :

Given a set of k linear equations of the form

 Li = bi (0 ≤ i < k) (1)
in which the Li are homogeneous linear expressions in the unknowns with natural coefficients and the bi are natural numbers, there exists a single equation
 M = c (2)
in which M is a homogeneous linear expression in the unknowns with natural coefficients and c is a natural number, such that (2) has the same natural solutions as (1).

Because the natural solutions of (1) are the common natural solutions of (3) and (4), as given by

 L0 = b0 L1 = b1 (3)
 and Li = bi for 2 ≤ 1 < (4)
it suffices to prove that (3) can be replaced by a single equation with the same natural solutions as (3).

Consider for natural P0 and P1, to be chosen later, the equation

 P0 * L0 + P1 * L1= P0 * b0 + P1 * b1 (5)
All solutions of (3) are solutions of (5). We shall show that and P0 and P1 can be chosen in such a way, that, conversely, all natural solutions of (5) are solutions of (3). We shall do so by choosing P0 and P1 in such a way that (5), considered as an equation in L0 and L1 , has (3) as its only natural solution; because all natural choices for the original unknowns will give rise to natural L0 and L1 , this is sufficient.

Considered as an equation in L0 and L1 , the general parametric solution of (5) is given by L0 = b0 + t * P1 L1 = b1 - t * P0 (where, to start with, t need not be a natural number). We shall choose a natural P0 and P1 in such a way that from natural L0 and L1 , viz.

 b0 + t * P1 ≥ 0 (6) b1 - t * P0 ≥ 0 (7) left-hand sides of (6) and (7) integer (8)
we can conclude t = 0 .

Choosing P1 > b , we derive from (6)

 t > -1 (9)

Choosing P0 > b1 , we derive from (7)

 t < 1 (10)

Choosing P0 and P1 furthermore such that gcd(P0, P1) = 1 , we derive From (8) that t must be integer; in view of (9) and (10) we conclude that t = 0 holds. Summarizing: (5) can replace (3) provided

 P0 > b1, P1 > b0 , gcd(P0, P1) = 1

*              *
*

Example. Let the given set be x = 1, y = 1, z = 1 . The first two equations can be combined by choosing P0 = 2 and P1 = 3, yielding:

 2*x + 3*y = 5 , z = 1 .
These two can be combined by choosing P0 = 2 and P1 = 7, yielding
 4*x + 6*y + 7*z = 17
for which (1,1,1) is, indeed, the only natural solution. (End of example.)

3 August 1976
Plataanstraat 5
NL-4565 NUENEN
The Netherlands

Transcribed by Martin P.M. van der Burgt
Last revision 2015-01-23 .